2004
DOI: 10.1002/arch.10128
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis δ‐endotoxin binding to brush border membrane vesicles of rice stem borers

Abstract: The receptor binding step in the molecular mode of action of five delta-endotoxins (Cry1Ab, Cry1Ac, Cry1C, Cry2A, and Cry9C) from Bacillus thuringiensis was examined to find toxins with different receptor sites in the midgut of the striped stem borer (SSB) Chilo suppressalis (Walker) and yellow stem borer (YSB) Scirpophaga incertulas (Walker) (Lepidoptera: Pyralidae). Homologous competition assays were used to estimate binding affinities (K(com)) of (125)I-labelled toxins to brush border membrane vesicles (BBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 35 publications
4
51
1
Order By: Relevance
“…Based on the toxin regions included in the Cry1Ab-Cry1Ac hybrid produced by HH1 rice (37), the binding specificity of this hybrid toxin is dictated by domain II of Cry1Ab and domain III of Cry1Ac. In agreement with previous reports (18,19), we detected high-affinity binding of both Cry1Ab and Cry1Ac toxins to BBMV proteins from C. suppressalis. While similar high-affinity Cry1Ab and Cry1Ac binding was detected for S. inferens BBMV proteins, we detected a drastic reduction in the concentration of binding sites for the two toxins in S. inferens BBMV compared to that in C. suppressalis BBMV.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the toxin regions included in the Cry1Ab-Cry1Ac hybrid produced by HH1 rice (37), the binding specificity of this hybrid toxin is dictated by domain II of Cry1Ab and domain III of Cry1Ac. In agreement with previous reports (18,19), we detected high-affinity binding of both Cry1Ab and Cry1Ac toxins to BBMV proteins from C. suppressalis. While similar high-affinity Cry1Ab and Cry1Ac binding was detected for S. inferens BBMV proteins, we detected a drastic reduction in the concentration of binding sites for the two toxins in S. inferens BBMV compared to that in C. suppressalis BBMV.…”
Section: Discussionsupporting
confidence: 93%
“…These high levels of resistance are expected in cases of field-evolved practical resistance to Bt crops (16). In the case of C. suppressalis, binding competition studies in larval brush border membrane vesicles (BBMV) revealed that Cry1A toxins share binding sites with Cry1Ba toxin (17) but they are not recognized by Cry2A, Cry9C, or Cry1C toxins (18,19). Diverse studies have suggested aminopeptidase-N and cadherin-like proteins as Cry1A binding sites in C. suppressalis BBMV (20,21).…”
mentioning
confidence: 99%
“…Therefore, combinations of Cry1A genes with other groups of Bt genes should be explored to prevent or delay the emergence of pest resistance. Based on the assay of ␦-endotoxin binding to brush border membrane vesicles of rice stemborers, it was proposed that Cry1A genes could be combined with Cry1C, Cry2A, or Cry9C for more durable resistance in transgenic plants (32).…”
Section: Progresses In Gene Identification and Development Of Gsrmentioning
confidence: 99%
“…The success of combining multiple Bt genes for resistance management is contingent on the individual toxins having different targets to prevent cross resistance developing [163][164][165]. Binding studies with various Cry toxins have been used to identify toxins with different binding sites in the lepidopteran midguts [105,166,167]. This information can be used to design combinations of Cry toxins that complement each other to delay the development of resistance to Bt crops.…”
Section: Management Of Resistance To Bt Cropsmentioning
confidence: 99%